PEMBERDAYAAN IBU MELALUI PRAKTIK DUKUNGAN KELUARGA UNTUK CEGAH STUNTING - Rokhaidah Rokhaidah; Lina Ayu marcelina; Lima Florensia (Jurnal Bakti Masyarakat Indonesia, 2022)
Depok City in August 2021 had a stunting prevalence of 3.5 percent. An important factor that affects stunting is knowledge. Good maternal knowledge can be used for stunting prevention efforts. Family support is also important to provide encouragement in the form of attention to family members and assist family members in solving health problems so that they will feel confident in dealing with problems. Partner problems are: the lack of understanding of mothers about family support in preventing stunting in children. The solution to the problems faced by partners in the Pasir Putih sub-district, Sawangan-Depok sub-district, is the Community Partnership Program (PKM) for empowering mothers through family support practices to prevent stunting by implementing health education on family support practices to prevent stunting in children. Implementation on 1-30 July 2022. The purpose of this Community Partnership Program is to increase the ability, willingness and awareness of the community in preventing stunting by recognizing stunting and through family support. Methods: Health Education using lecture and discussion methods. Results: after this PKM activity, the partners' knowledge about stunting increased with the results before the test that the mother had good knowledge of 35% to 80% at the time of the test and the practice of good family support at the time of the test increased from 83% to 94% during the test. Conclusion: Health education is very important for mothers as an effort to prevent stunting through family support. ABSTRAK: Kota Depok pada Agustus 2021 memiliki prevalensi stunting sebesar 3,5 persen, Faktor penting yang mempengaruhi stunting adalah pengetahuan. Pengetahuan ibu yang baik dapat digunakan untuk upaya pencegahan stunting. Dukungan keluarga juga menjadi penting untuk memberikan dorongan berupa perhatian ke anggota keluarga dan membantu anggota keluarga dalam menyelesaikan masalah kesehatan sehingga akan merasa percaya diri dalam menghadapi masalah. Permasalahan mitra adalah: belum terbentuknya pemahaman ibu tentang dukungan keluarga dalam pencegahan stunting pada anak. Solusi bagi masalah yang dihadapi mitra di kelurahan Pasir Putih kecamatan Sawangan-Depok adalah dengan Program Kemitraan Masyarakat (PKM) pemberdayaan ibu melalui praktik dukungan keluarga cegah stunting dengan implementasi edukasi kesehatan tentang praktik dukungan keluarga untuk cegah stunting pada anak. Pelaksanaan kegiatan pada tanggal 1-30 Juli 2022. Tujuan dari Program Kemitraan Masyarakat ini adalah untuk meningkatkan kemampuan, kemauan dan kesadaran masyarakat dalam mencegah stunting dengan cara mengenali penyakit stunting serta melalui dukungan keluarga. Metode: Edukasi Kesehatan dengan menggunakan metode ceramah dan diskusi. Hasil: setelah kegiatan PKM ini pengetahuan mitra tentang stunting meningkat dengan hasil sebelum tes ibu berpengetahuan baik sebanyak 35% menjadi 80% pada saat post tes dan praktik dukungan keluarga baik pada saat pretest  84% meningkat menjadi 94% saat posttest. Kesimpulan: edukasi Kesehatan sangat penting bagi ibu sebagai upaya pencegahan stunting melalui dukungan keluarga.